New developments towards the management of severe cases of tracheobronchomalacia - van der Zee, David C. (Journal of Thoracic Disease, 2016)
Tracheobronchomalacia is a severe anomaly that can lead to acute life-threatening events, due to collapse of the upper airways (1). The congenital form is the most frequent occurring, usually in conjunction with esophageal atresia (2), but sometimes acquired tracheobronchomalacia may occur as described by Huang et al. (3).